Conclusions of the International Symposium “Protection of the Black Sea Ecosystem and Sustainable Management of Maritime Activities“ PROMARE 2015 - Zaharia, Tania (Cercetări Marine - Recherches Marines, 2015)
Between 29-31 October 2011, in Constanța, Romania, at the headquarters of the National Institute for Marine Research and Development “Grigore Antipa“, the proceedings of the International Symposium “PROTECTION OF THE BLACK SEA ECOSYSTEM AND SUSTAINABLE MANAGEMENT OF MARITIME ACTIVITIES “, VIIth edition, PROMARE 2015, were carried out.